Design and analysis of high linearity mixer using subharmonic technique. (9th August 2018) - Modanlou, Shahram; Miar‐Naimi, Hossein; Gholami, Mohammad
Summary: In this article, a new technique for reducing second‐order and third‐order intermodulation (IM2 and IM3) for an output current of the subharmonic mixer is presented. First, to reduce second‐order and third‐order of the Volterra's kernel, IM2 current injection technique has been used. By the auxiliary path, the IM2 current which has been generated in the doubler with the phase difference of 180° relative to inherent IM2 of the output is injected into the output node. Also, this produced IM2 in the frequency doubler has been injected into the circuit by another auxiliary path, so that, in the output, an IM3 with opposite phase of inherent IM3 of the output mixer's current is presented. Besides, to easier design, the Volterra series expansion is used and equations related to Volterra kernels of the output current are extracted. Furthermore, the noise of the auxiliary path transistors connected to the output can be neglected because of the small g m of their transistors compared to the main path. The results of simulations by ADS simulator in 0.18‐μm TSMC technology show that the proposed technique has simultaneously improved the values of IIP3 and IIP2 up to 21 and 92 dBm, compared to conventional subharmonic mixers. Abstract : In this article, a new technique for improving mixer linearity is presented. The results of simulations in 0.18‐ μm TSMC technology show that the proposed technique has simultaneously improved the IIP3 and IIP2 up to 18 and 23 dBm respectively.